Effects of replacing wheat flour with detoxified ginkgo nut powder on lipid metabolism of obese C57BL/6J male mice - Haiying Liu (Taylor & Francis Group, 2018)
Effects of detoxified ginkgo nut powder (DGP) on lipid metabolism of obese mice were evaluated. Mice were divided into four groups: normal group (NC), hyperlipidaemic group (HC, high-fat feed), HC/DGP group (high-fat diet + DGP), and HC/flour group (HC/WF, high-fat diet + flour). After 18 weeks, liver and body fat weights of HC/DGP were significantly lower than those of HC and HC/WF, but similar to those of NC. The serum and hepatic levels of serum triglyceride, total cholesterol, low-density lipoprotein cholesterol, leptin and resistin in HC/DGP were similar to those in NC but significantly lower than those in HC and HC/WF. In addition, the expression levels of PPARα (peroxisome proliferator-activated receptor alpha) in liver and of hormone-sensitive lipase, adipose triglyceride lipase, and monoacylglycerol lipase in epididymal fat were higher in HC/DGP than in other groups. The results revealed that DGP may reduce inflammation and promote normal lipid metabolism.